Thermal drone monitoring of arboreal primates in a post-coal mining area in South Kalimantan, Indonesia - SOFIAN ISKANDAR; HANIFULLAH HABIBIE; ABDUL RAHMAN HAFIF; DODIK CHOIRON; RIZA NOVIAN; MEKKA RIADHAH; DIDIK TRIWIBOWO; RIO RIZKY KURNIAWAN; ADINDA AINUN MARDIAH (Society for Indonesian Biodiversity, 2025)
Abstract. Iskandar S, Habibie H, Hafif AR, Choiron D, Novian R, Riadhah M, Triwibowo D, Kurniawan RR, Mardiah AA. 2025. Thermal drone monitoring of arboreal primates in a post-coal mining area in South Kalimantan, Indonesia. Biodiversitas 26: 4673-4684. PT Adaro Indonesia in South Kalimantan, Indonesia, is committed to rehabilitating natural habitat and restoring biodiversity in post-mining areas. The proboscis monkey (Nasalis larvatus) and silvery lutung (Trachypithecus cristatus) are arboreal primates and protected species in accordance with regulations issued by Indonesian Minister of Environment and Forestry No. P.106/MENLHK/SETJEN/KUM.1/12/2018, the IUCN Redlist, and Appendix I of CITES. The monitoring program aims to monitor the population and habitat of these primates in Paringin, South Kalimantan, an area impacted by mining activities, using thermal drone technology as a non-invasive, efficient survey method. Thermal drones were deployed to identify primate sleeping sites with greater precision. Optimal flight parameters included a total flight distance of 41 km, 12 waypoints, a flight duration of 14 minutes and 23 seconds, a speed of 15 m/s, and an altitude of 120 meters—ensuring adequate canopy clearance and visibility. This method enabled reliable detection of primate groups, allowing accurate estimates of population density: 21.5 ind/km² in Post-Coal Mining Area and 6.61 ind/km² in BUPER for proboscis monkeys. Meanwhile, silvery lutungs have 25.3 ind/km² in Post-Coal Mining Area and 4.96 ind/km² in BUPER. However, age and sex composition could not be detected from thermal imagery. Vegetation analysis of the pit lake area recorded 21 tree species, with 664 trees, 1,431 poles, 2,096 stakes, and 3,100 seedlings, indicating regenerating habitat structure. The availability of food species and habitat suitability were identified as the primary drivers of primate distribution in the area. Thermal drone photography is capable of counting the total number of individuals in a detected group, but it may not be able to identify the composition of individuals based on age and sex categories.